Effects of recreational fishing on zooplankton communities of drainage system reservoirs at an open‐pit mine - Goździejewska, Anna Maria; Skrzypczak, Andrzej Robert; Koszałka, Jacek; Bowszys, Magdalena (Fisheries management and ecology, 2020)
The use of artificial water bodies for angling is a popular practice, especially in industrial and urbanised areas where natural water bodies are lost. In this study, the zooplankton structure dynamics and water quality at three strip mine drainage system reservoirs were assessed with different types of recreational fishery exploitation: K1—intensive angling using the catch‐and‐release model, K2—lowest angling pressure and higher share of predatory fishes and K3—moderate fishing, that is limiting groundbait quantities and eliminating non‐predatory fishes by anglers. The null hypothesis tested was that recreational fishing does not affect the biotic and abiotic conditions of reservoirs. The significance of each environmental variable was tested using redundancy analysis (RDA). The highest nutrients and chlorophyll a concentration, turbidity level and organic matter content occurred in K1. Zooplankton diversity was the lowest under these conditions; protozoa and larval stages of copepods dominated. In reservoirs where sustainable fishing was implemented (K2, K3), trophic parameters of water were lower, on average, by 25%, turbidity by 30%, and productivity by 35–70%. Zooplankton diversity was significantly higher; rotifers and small cladocerans dominated. The choice of recreational fishing model determines the functionality and biological potential of the reservoir.